Neuro-Modulating Effects of Honokiol: A Review - Woodbury, Anna; Yu, Shan Ping; Wei, Ling; Garcia, Paul (Frontiers in Neurology, 2013)
Honokiol is a polyphenolic compound that exerts neuroprotective properties through a variety of mechanisms. It has therapeutic potential in anxiety, pain, cerebrovascular injury, epilepsy, and cognitive disorders including Alzheimer’s disease. It has been traditionally used in medical practices throughout much of Southeast Asia, but has now become more widely studied due to its pleiotropic effects. Most current research regarding this compound has focused on its chemotherapeutic properties. However, it has the potential to be an effective neuroprotective agent as well. This review summarizes what is currently known regarding the mechanisms involved in the neuroprotective and anesthetic effects of this compound and identifies potential areas for further research.